Impact of ERP system on productivity improvement: some empirical findings - Zainol, Zaini; Abu Bakar , Zaitun (Universiti Teknologi MARA (UiTM), 2011)
The aim of this study is to investigate whether enterprise resource planning (ERP) investment brought productivity improvement to the organization as promised by the system provider. We used three productivity indicators adopted from the Malaysia Productivity Corporation.These indicators are competitiveness indicator,labour productivity indicator and capital productivity indicator. A total of four manufacturing companies were selected. These companies have been using ERP based systems for a minimum three years. Our findings showed mixed results. Of the three indicators, the labour productivity indicator had shown positive contribution whereas the remaining two indicators i.e. competitiveness and capital productivity had resulted in negative feedback. Generally, these indicators seem to show that the increase in labour cost was greater than the increase in the value-added created as a result of adopting an ERP system.